Driving Business Performance Through Entrepreneurial Orientation and Innovation - Danendra, Rafi; Rofiaty (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the effects of entrepreneurial orientation and innovation on firm performance among chip businesses in Batu City. Design/Methodology/Approach – This study employs an explanatory quantitative research design. Data were collected from 71 chip business owners in Batu City using a saturated sampling technique. The data were processed and analyzed using IBM SPSS version 25.0 to examine the relationships between entrepreneurial orientation, innovation, and firm performance through statistical testing. Findings – The results indicate that entrepreneurial orientation has a positive and significant effect on firm performance. This finding demonstrates that entrepreneurial orientation enables businesses to improve performance by being more responsive to market opportunities and competitive changes. Innovation also has a positive and significant effect on firm performance, indicating that product and process improvements, including changes in production raw materials, contribute to enhanced business outcomes. Originality/Value This research is original in empirically examining the combined influence of entrepreneurial orientation and innovation within a regional chip industry context. The findings provide practical value by guiding business owners to improve performance through opportunity-seeking behavior and production innovation.